2021
DOI: 10.3390/toxins13110786
|View full text |Cite
|
Sign up to set email alerts
|

Cyanotoxins and Food Contamination in Developing Countries: Review of Their Types, Toxicity, Analysis, Occurrence and Mitigation Strategies

Abstract: Cyanotoxins have gained global public interest due to their potential to bioaccumulate in food, which threatens human health. Bloom formation is usually enhanced under Mediterranean, subtropical and tropical climates which are the dominant climate types in developing countries. In this context, we present an up-to-date overview of cyanotoxins (types, toxic effects, analysis, occurrence, and mitigation) with a special focus on their contamination in (sea)food from all the developing countries in Africa, Asia, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 201 publications
(346 reference statements)
1
16
0
Order By: Relevance
“…However, these two studies also reported decreased concentrations of paralytic shellfish toxins respectively upon variation of particle size (exposure to 1 μm MP) and prolonged exposure time. Furthermore, micro-and nanoplastics can directly alter the cyanobacterial production of microcystins, a class of environmental toxins which also play an emerging role as food contaminants due to the increased anthropogenic activities and climate change (Abdallah et al, 2021). Independent studies (X.…”
Section: Impact Of Micro-and Nanoplastics On Bacterial Toxin Producti...mentioning
confidence: 99%
“…However, these two studies also reported decreased concentrations of paralytic shellfish toxins respectively upon variation of particle size (exposure to 1 μm MP) and prolonged exposure time. Furthermore, micro-and nanoplastics can directly alter the cyanobacterial production of microcystins, a class of environmental toxins which also play an emerging role as food contaminants due to the increased anthropogenic activities and climate change (Abdallah et al, 2021). Independent studies (X.…”
Section: Impact Of Micro-and Nanoplastics On Bacterial Toxin Producti...mentioning
confidence: 99%
“…Cyanotoxins can be produced in eutrophic waterbodies during blooms of photosynthetic, eukaryotic organisms called cyanobacteria [1][2][3][4][5][6][7][8]. Multiple studies and reviews have documented the occurrence of cyanotoxins in different foods [9,10]. The sedentary nature of agriculture allows for the accumulation of these harmful compounds in food crops when vital irrigation water is contaminated with these toxins.…”
Section: Introductionmentioning
confidence: 99%
“…The worldwide spread of toxic cyanobacterial blooms has become a global threat to freshwater resources due to the production of cyanotoxins [ 1 , 2 , 3 ]. One of the major cyanotoxins is microcystin (MC), and MC-rich waters are frequently used for crop irrigation and human/livestock consumption and, thus, reach the food chain [ 4 , 5 , 6 ]. MC causes serious health problems such as liver cancer, colorectal cancer [ 7 ], and malnutrition via nutrient deficiency in crops irrigated with MC-contaminated water.…”
Section: Introductionmentioning
confidence: 99%